MRSA Strains in Nepalese Rhesus Macaques (Macaca mulatta) and Their Environment - Roberts, Marilyn C.; Joshi, Prabhu Raj; Monecke, Stefan; Ehricht, Ralf; Müller, Elke; Gawlik, Darius; Paudel, Saroj; Acharya, Mahesh; Bhattarai, Sankalpa; Pokharel, Sujana; Tuladhar, Reshma; Chalise, Mukesh K.; et al. (Frontiers in Microbiology, 2019)
This study looked at 227 saliva samples from Rhesus macaques (Macaca mulatta) and 218 samples from the surrounding environments. From these samples, MRSA isolates were collected from Rhesus saliva samples (n=13) and environmental samples (n=19) near temple areas in Kathmandu, Nepal. For comparison, selected MRSA isolates (n=5) were obtained from patients with wound infections from a Kathmandu hospital. All isolates were characterized using Abbott StaphyType® DNA microarrays. Eighteen isolates (62%) from monkeys (n=4; 31%) and environmental samples (n=14; 74%), were CC22-MRSA-IV. Most (n=16) of them carried both, the PVL locus and toxic shock toxin gene (tst1), an unusual combination which is the same as in previously characterized strain from Nepalese macaques and pigs. The five human isolates also belonged to that strain type. Eight monkey MRSA isolates were CC361-MRSA-IV. One MRSA from a monkey and one from an environmental sample, were CC88-MRSA-V. Other environmental MRSA included one each, CC121-MRSA-VT, and CC772 -MRSA-V. Two were CC779-MRSA-VT, potentially a novel clone. All MRSA carried the blaZ gene. The aacA-aphD, dfrA and erm(C) genes were very common in isolates from all sources. One macaque MRSA carried the resistance genes aphA3 and sat, neither previously identified in primate MRSA isolates. This current study suggests that humans could be a potential source of the MRSA in the macaques/environment and transmission may be linked to humans feeding the primates and/or living in close proximity to each other.